The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1007/s10802-018-0491-x
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the Structure and Measurement of Inattentive, Hyperactive, and Impulsive Behaviors from Preschool to Grade 4

Abstract: Attention Deficit/Hyperactivity Disorder (ADHD) is a complex and heterogeneous disorder consisting of inattentive and hyperactive/impulsive behaviors. Although, the multidimensionality of ADHD is widely accepted, questions remain regarding the extent to which the components of this disorder are overlapping or distinct. Further, although the same measures are generally used to assess inattentive, hyperactive, and impulsive behaviors across childhood, it has been argued that the structure and measurement of inat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 40 publications
(49 reference statements)
2
17
0
Order By: Relevance
“…In keeping with much prior research (e.g., [18][19][20][21][22][23][24][25][26]), the traditional goodness of fit indices showed that the bifactor models provided a better fit than the correlated models in both samples. Recently, some concerns have been raised about relying on or overemphasizing traditional goodness of fit indices as these indices may favor the less constrained model possessing more parameters such as the bifactor model and due to the potential tendency to overfit data ascribed to the bifactor models [37][38][39].…”
Section: Bifactor Vs Correlated Modelssupporting
confidence: 75%
See 3 more Smart Citations
“…In keeping with much prior research (e.g., [18][19][20][21][22][23][24][25][26]), the traditional goodness of fit indices showed that the bifactor models provided a better fit than the correlated models in both samples. Recently, some concerns have been raised about relying on or overemphasizing traditional goodness of fit indices as these indices may favor the less constrained model possessing more parameters such as the bifactor model and due to the potential tendency to overfit data ascribed to the bifactor models [37][38][39].…”
Section: Bifactor Vs Correlated Modelssupporting
confidence: 75%
“…In these models, each symptom loads on the general factor and on one of the specific factors, and the correlations between all specified factors are restricted to zero (i.e., orthogonality) [14,16]. Studies have quite consistently supported bifactor models of ADHD over traditional correlated models across diverse ages, informants, measures, and samples (e.g., [18][19][20][21][22][23][24][25][26]).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although both are expressed through lack of control, impulsivity could be better understood as a lack of cognitive inhibition and hyperactivity as a lack of motor inhibition. To verify this, some authors have evaluated the levels of hyperactivity and impulsivity in a sample of more than 10,000 healthy children, concluding emphatically that the measures of hyperactivity and impulsivity address different constructs [52]. In this regard, it is not complicated to imagine a person of any age who can be very energetic, in terms of activity, and yet be extremely reflective in terms of decision making.…”
Section: Hyperactivity and Impulsivity: Different Concepts Same Diagmentioning
confidence: 99%